Fosca Revisited: The Vampire-Woman in Tarchetti and Ettore Scola’s Passione d’amore - Bettella, Patrizia (Spunti e Ricerche, 2016)
This paper revisits the novel Fosca by Igino Ugo Tarchetti and Passione d’amore (1981), its film adaptation by Ettore Scola. It finds that there is a vampiric subtext embedded in the novel and in the film. Both rework some themes of Tarchetti’s poetry (particularly "Memento") of his Fantastic Tales and of the Scapigliatura poetry. Fosca is a psychic vampire in the form defined by Nina Auerbach: rather than sucking blood she depletes her victim/lover of energy. Scola’s film also draws on the German expressionist cinema of F. W. Murnau who, in 1922, directed Nosferatu, eine Symphonie des Grauens. Scola draws visual parallels with Murnau’s Nosferatu and adds to the novel’s plot an epilogue, where he establishes a link between Fosca as the kissing vampire and Tarchetti’s skeleton woman, a ubiquitous female presence in his poems and tales.